Marketing aspects of consumption of Hungarian pork meat - Kárpáti , László; Torda, Kitti (Applied Studies in Agribusiness and Commerce, 2009)
The most important aim of authors’ study is to get to know the Hungarian pork consumption in our days. Our aim is set to estimate pork meat consumption and purchasing habits of consumers who are living in Eastern part of Hungary. The pork section is influenced negatively by several factors nowadays, which have a clear effect on the pork consumption and cause its declination. During the research work a questionnaire survey was made in 2007 and 2008. 1089 persons in different locations of Eastern Hungary were altogether asked. The data were evaluated by statistic hypothesis testing. Based on the evaluation a clear picture was got about the consumers’purchasing and consuming habits, and their ideas, opinions about the Hungarian pork as a food and as an item wearing a kind of national behaviour. Through many questions the volume of consumption was explored, and the pork’s proportion was compared to the rest of other meat types. It is verifiable that the pork consumption can be handled as a national habit, which is not the same by different age groups and educational qualifications. The importance of some factors during purchasing was also examined. Exceptionally important factors are: quality, the appearance, the origin and the price, that were mostly considered by the customers.The effect of pork promotion advertisements and its evaluation by the customers were surveyed too, which in connection with the efficiency showed a fairly stable picture both in 2007 and in 2008. The examination of price elasticity showed that this figure is influenced not just by the product group itself, but the purchasing power of the costumers, as well.